Origin and Evolution of the Iron-Rich Upper Unit and Fe–Ti–V Mineralization of the Neoarchean Lac Doré Layered Intrusion, Chibougamau, Québec. (8th February 2022) - Mokchah, Nesrine; Mathieu, Lucie
Abstract: The Lac Doré Complex (LDC) is a metamorphosed Neoarchean (ca. 2728 Ma) tholeiitic layered intrusion with an estimated thickness of 7–8 km. The Layered zone (magnetitite, anorthosite, and gabbro mostly, and ferrodunite locally) is located in the upper part of the LDC, and it corresponds to an Fe–Ti oxide-bearing unit currently being explored for Fe–Ti–V magmatic deposits. Previous studies documented lithological, textural, and chemical heterogeneities in the Layered zone from the NW, NE, and S limbs of the LDC. This study integrates detailed chemical and petrological investigation of Fe-rich rocks across the Layered zone to evaluate the impact of magmatic processes (contamination, magma replenishment events, and fractional crystallization) on the evolution of the upper part of the LDC. Field data point to fractional crystallization (upward increase of quartz, apatite, and ilmenite, and decrease of titanomagnetite) and to efficient mineral sorting within flow currents (modal layering) in the S limb, where the Layered zone is thick, possibly as a result of frequent replenishment events. Petrological observations and bulk rock chemistry indicates that the magma emplaced at the NW limb was more evolved (Si richer) than the Fe-rich magmas emplaced at the NE and S limbs, explaining the limited economic potential of the NW limb. The chemistry of Fe–Ti oxides indicates that the least evolved Fe-rich magma (magma most enriched in V, Cr, and Ni) emplaced at the NE limb and subsequently interacted with Si–Ca–poor carbonate-facies iron formation. The chemistry of Fe–Ti oxides, as well as ƒO2 estimates, points to additional chemical heterogeneities across the Layered zone, which are interpreted to result from several injections of a chemically heterogeneous residual tholeiitic melt (Fe rich) followed by inefficient homogenization process. We conclude that Fe-rich residual melts produced by prolonged crystallization of silicates during most of the evolution of the LDC were extracted from the Lower zone (anorthosite- and gabbro-dominated unit) and migrated upward to form the Layered zone. Successive extraction of the Fe-rich melt in response to regional and/or local deformation event translates as replenishment events for the Layered zone that then evolved through contamination (NE limb), fractional crystallization (NW, NE, and S limbs), and mineral sorting (S limb).